Front Matter Jurnal TRI DHARMA MANDIRI Volume 1 Nomor 2 - Yunita, Ema Pristi (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2021)
-